2017
DOI: 10.1371/journal.pone.0172059
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of the HA and NA genes between vaccine and seasonal influenza A(H3N2) strains in Korea

Abstract: Seasonal influenza is caused by two influenza A subtype (H1N1 and H3N2) and two influenza B lineage (Victoria and Yamagata) viruses. Of these antigenically distinct viruses, the H3N2 virus was consistently detected in substantial proportions in Korea during the 2010/11-2013/14 seasons when compared to the other viruses and appeared responsible for the influenza-like illness rate peak during the first half of the 2011/12 season. To further scrutinize possible causes for this, we investigated the evolutionary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The pepitope model was used to quantify antigenic distance between the circulating strains and the corresponding vaccine strains. In several previous studies, the results of the the pepitope model showed a vaccine mismatch of A(H3N2) in the 2014/15 and 2015/16 seasons, which was consistent with the particular situation at that time 40,41 . Since 2016, the component of seasonal in uenza vaccines for the southern hemisphere is A/Hong Kong/4801/2014 belonging to clade 3C.2a.…”
Section: Discussionsupporting
confidence: 81%
“…The pepitope model was used to quantify antigenic distance between the circulating strains and the corresponding vaccine strains. In several previous studies, the results of the the pepitope model showed a vaccine mismatch of A(H3N2) in the 2014/15 and 2015/16 seasons, which was consistent with the particular situation at that time 40,41 . Since 2016, the component of seasonal in uenza vaccines for the southern hemisphere is A/Hong Kong/4801/2014 belonging to clade 3C.2a.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, based on our phylogenetic analysis (Supplementary file 2) and two recent reports [21,22], we also determined the NA genotypes of these viruses (Table S1). In the 2014–2015 influenza season, the dominant genotype was 3C.3, which continued to circulate during our surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…Our phylogenies of three gene segments uniformly depicted that endemic SFTSVs have mainly caused human infection within limited local areas. However, even with the genetic homogeneity of endemic SFTSVs by countries, we occasionally observed polyphyletic genealogy in the phylogenies likely depicting the long-distance spread of endemic SFTSVs among China, Japan, and South Korea [ 27 , 30 ], but not frequent as the phylogenies of influenza virus or SARS-CoV-2 with highly intensive international spread [ 45 , 46 ]. Chinese SFTSV genotype B was most prevalent on Zhoushan Island located in the East China Sea but also caused human infection in South Korea and Japan [ 27 ].…”
Section: Discussionmentioning
confidence: 99%